2008
DOI: 10.1900/rds.2008.5.225
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Protein Modifications in Type 1 Diabetes - Genetic Studies with PCMT1, the Repair Enzyme Protein Isoaspartate Methyltransferase (PIMT) Encoding Gene

Abstract: BACKGROUND: Posttranslational protein modifications have been implicated in the development of autoimmunity. Protein L-isoaspartate (D-aspartate) O-methyltransferase (PIMT) repairs modified proteins and is encoded by PCMT1, located in a region linked to type 1 diabetes (T1D), namely IDDM5. AIM: To evaluate the association between genetic variations in the PCMT1 gene and T1D. METH-ODS: Firstly, PCMT1 was sequenced in 26 patients with T1D (linked to IDDM5) and 10 control subjects. The variations found in PCMT1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Moreover, the overexpression of PIMT in Escherichia coli or drosophila melanogaster increases the lifespan and survival under the heat stress [26], [27]. PIMT plays a role in the repair and/or degradation of damaged proteins and involves in the pathogenesis of diabetes mellitus and atherosclerosis [9], [28], [29]. We demonstrated here that gly-LDL down-regulated PIMT in HUVEC.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, the overexpression of PIMT in Escherichia coli or drosophila melanogaster increases the lifespan and survival under the heat stress [26], [27]. PIMT plays a role in the repair and/or degradation of damaged proteins and involves in the pathogenesis of diabetes mellitus and atherosclerosis [9], [28], [29]. We demonstrated here that gly-LDL down-regulated PIMT in HUVEC.…”
Section: Discussionmentioning
confidence: 58%
“…PCMT1 expression decreases with age, which may partially explain the increases of damaged protein levels and pathogenesis of several age-related diseases, such as neurodegenerative diseases, [36] diabetes mellitus, [37] and premature ovarian failure. [38] Moreover, a recent study has shown that methylation of histone H4 at aspartate 24 by the PCMT1 enzyme was involved in contribution to protein homeostasis via proteasome activation utilizing a methylation site-specific antibody.…”
Section: Discussionmentioning
confidence: 99%
“…PIMT is a conserved and nearly ubiquitous enzyme that can recognise and repair isomerised Asn and Asp residues in proteins, which have been demonstrated to catalyse the first step in a process that can convert L-isoaspartyl residues in peptides to normal L-aspartyl residues [49]. This "repair" reaction helps to maintain proper protein conformation by preventing the accumulation of potentially dysfunctional proteins.…”
Section: Proteins Related To Molecular Functionmentioning
confidence: 99%